Measurement and correction of transverse chromatic offsets for multi-wavelength retinal microscopy in the living eye - Harmening, Wolf M. (Optical Society of America, 2012)
A special challenge arises when pursuing multi-wavelength imaging of retinal tissue in vivo, because the eye’s optics must be used as the main focusing elements, and they introduce significant chromatic dispersion. Here we present an image-based method to measure and correct for the eye’s transverse chromatic aberrations rapidly, non-invasively, and with high precision. We validate the technique against hyperacute psychophysical performance and the standard chromatic human eye model. In vivo correction of chromatic dispersion will enable confocal multi-wavelength images of the living retina to be aligned, and allow targeted chromatic stimulation of the photoreceptor mosaic to be performed accurately with sub-cellular resolution.